Estimation of Dynamic Labor Demand Schedules under Rational Expectations - Sargent, Thomas J. (Journal of Political Economy, 1978)
A dynamic linear demand schedule for labor is estimated and tested. The hypothesis of rational expectations and assumptions about the orders of the Markov processes governing technology impose over-identifying restrictions on a vector autoregression for straight-time employment, overtime employment, and the real wage. The model is estimated by the full information maximum likelihood method. The model is used as a vehicle for re-examining some of the paradoxical cyclical behavior of real wages described in the famous Dunlop-Tarshis-Keynes exchange.